The Role of TNF- α Inhibitors in The Management of Gout Arthritis and Its Comparison with Other Modalities - Nita Parisa; Valyn Theodra Tantoro; Masayu Syarinta Adenina; Bintang Arroyantri Prananjaya (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2024)
Background: Gout arthritis is caused by the deposition of monosodium urate crystals in the joints, which can cause significant pain, swelling, and recurring inflammation, particularly in the big toe. Inflammatory mediators are critical to the beginning and duration of the inflammatory response in gout arthritis. Gout is mediated by TNF-α, ILs, and the NLRP3 inflammasome, which promotes macrophages, monocytes, and neutrophils, leading to inflammatory reactions. TNF-α acts as a potent inflammatory mediator by stimulating the expression of other inflammatory cytokines, adhesion molecules, and matrix metalloproteinases (MMPs). TNF-α interacts with particular receptors and activates intracellular signaling pathways, leading to leukocyte recruitment, NLRP3 inflammasome activation, and the release of other inflammatory mediators. Objective: This article is a review article in which the researchers examine the current state of understanding regarding the role of TNF-α as a major inflammatory mediator in gout arthritis, deepen the understanding of TNF-α in gout inflammation, and explore its potential as a therapeutic target. Method: It involvedsystematically searching relevant databases, selecting studies based on inclusion criteria, and synthesizing findings to identify trends, gaps, and the current state of knowledge on the topic. Result: The results of this review article indicated that TNF-α plays a crucial role in joint inflammation by triggering the release of pro-inflammatory cytokines and stimulating neutrophil infiltration into the joints. Conclusion: Thus, Inhibiting TNF-α can reduce inflammation and improve symptoms in people with gout arthritis.